French Family Cooking - Clements, Carole; Wolf-Cohen, Elizabeth (London, 2008)
This book brings together a fabulous selection of recipes from all over France, that evokes the authentic flavours of this rich and diverse cuisine. The preparation and presentation of these recipes is uncontrived and uncomplicated and suitable for a var
Keywords: Cooking, French; Cookbook